Ultrasound-assisted Synthesis of Nitrogen and Oxygen Containing Heterocycles - Wahan, Simranpreet K.; Bhargava, Gaurav; Chawla, Pooja A. (Current Organic Chemistry, 2023)
Ultrasound is well explored in the preparation of several heterocycles as it is an eco-friendly, safer and cheaper technique compared to the previous conventional synthetic approach. Ultrasonication offers a great deal of interest for chemists as it not only lowers the reaction time but also markedly reduces the use of hazardous chemicals and enhances the purity of synthesized compounds. Since the application of ultrasound waves acts as a nonpolluting energy source, therefore, it is an area of great importance in the field of green and sustainable chemistry. Also, nitrogen and oxygen-based pharmaceuticals have been found to be a beneficial tool for modifying solubility, lipophilicity, polarity and other important pharmacokinetic parameters which aid in optimizing ADMET characteristics of drug candidates. Further, nitrogen and oxygen-containing compounds have been reported to exhibit antibacterial, antiviral, anti-inflammatory, anticancer, analgesic, antihyperglycemic action etc. Therefore, the review focues to coveron covering the latest applications of ultrasonication in the preparation of oxygen and nitrogen nitrogencontaining heterocycles holding immense importance in therapeutically active molecules, which will aid new researchers in their ongoingnd future research.
Keywords: mild conditions